The impact of place-based policies on perceived regional living conditions across German labor market regions: Examining the impacts on migration flows - Sven Wardenburg; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2019)
The paper analyzes the impact of the two major German regional dev elopment and redistribution policies, the municipal fiscal equalization scheme and the economic funds GRW, on perceived regional living conditions, measured through inte rregional migration between German labor market regions. Using a spatial v ector-autoregres- sive panel model (SpVar), we find evidence that equalization transf ers have a significant positive impact on perceived living conditions and contribute to the aim of regional equity. These effects are especially found for regions with low endogenous fiscal capacities. GRW funding reveals no significant effects on net mi gration rates in total, but short-term effects in rural regions.
Keywords: C33; R23; R58; O38; 330; amenities; impulse-response functions; living conditions; migration; policy; SpVar